Winds from the north : Canadian contributions to the Pentecostal movement - Wilkinson, Michael, 1965-; Althouse, Peter. (Religion in the Americas, 2010)
Much of the scholarly focus on early twentieth-century Pentecostalism is dominated by the origins debates of the United States. The polarization between those who argue for Parham's theological contribution or Seymour's African American experiential contribution is well known. Beyond these debates scholars typically focus on the role of Americans in the development of Pentecostalism. However, the Hebden mission in Toronto, Canadian women, and the Latter Rain revival illustrate the transnational and innovative qualities of the movement. This book contextualizes the global story of Pentecostalism with some important and often neglected contributions by Pentecostals in Canada and their influence on Pentecostalism in the United States and the world.